2011
DOI: 10.1590/s1984-70332011000400010
|View full text |Cite
|
Sign up to set email alerts
|

Minimum number of common bean plants per plot to assess field resistance to white mold

Abstract: -This study aimed to determine the minimum number of plants per plot to assess the field resistance in common bean to white mold. Thirteen cultivars were inoculated with six isolates of Sclerotinia sclerotiorum and evaluated in a randomized block design with three replications and plots consisting of 1-m rows with 15 plants. Plants were inoculated by the straw test as proposed by Petzoldt and Dickson (1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…The germplasm screening methods for white mold in common bean can be classified into those using to identify susceptible and resistant white mold genotypes in dry bean and soybean. Carneiro et al (2011) used the cut-stem method to evaluate 13 common bean cultivars against six isolates of S. sclerotiorum and to determine the minimum number of plants per plot required for the field test. They found no significant interaction between the pathogen isolates and cultivars, and eight plants per plot were adequate to assess the disease reaction.…”
Section: Germplasm Screening Methodsmentioning
confidence: 99%
“…The germplasm screening methods for white mold in common bean can be classified into those using to identify susceptible and resistant white mold genotypes in dry bean and soybean. Carneiro et al (2011) used the cut-stem method to evaluate 13 common bean cultivars against six isolates of S. sclerotiorum and to determine the minimum number of plants per plot required for the field test. They found no significant interaction between the pathogen isolates and cultivars, and eight plants per plot were adequate to assess the disease reaction.…”
Section: Germplasm Screening Methodsmentioning
confidence: 99%
“…Kim et al (2000) found that the genotype-by-environment interaction was significant in field evaluations. However, field evaluation through the straw test ensures the presence of the pathogen and development of the disease using the same crop conditions, without the space limitation that occurs in controlled environments (Carneiro et al, 2011). Moreover, the ability to assess both physiological resistance and escape mechanisms is another advantage of field inoculation under crop conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For analysis of the host-by-pathogen interaction, the data regarding reaction of genotypes to S. sclerotiorum isolates have been commonly assessed by ANOVA. However, a methodology using a partial diallel arrangement, as proposed by Melo and Santos (1999), has proven to be efficient in distinguishing horizontal and vertical resistance, pathogen aggressiveness, and estimating the genetic effect of resistance from each line and aggressiveness from each isolate (Buiate et al, 2010;Carneiro et al, 2011;Pereira, 2013). A GGE biplot analysis is another methodology that may be used to determine the levels of host resistance and isolate aggressiveness (Yan and Kang, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…No caso do modelo do CV relativo (CARNEIRO et al, 2011), a curva foi ajustada a partir do seguinte modelo teórico:…”
Section: Methodsunclassified